Curricular integration of social medicine: a prospective for medical educators. Issue 1 (1st January 2016) - Vanderbilt, Allison A.; Baugh, Reginald F.; Hogue, Patricia A.; Brennan, Julie A.; Ali, Imran I.
Abstract : In the United States, the health of a community falls on a continuum ranging from healthy to unhealthy and fluctuates based on several variables. Research policy and public health practice literature report substantial disparities in life expectancy, morbidity, risk factors, and quality of life, as well as persistence of these disparities among segments of the population. One such way to close this gap is to streamline medical education to better prepare our future physicians for our patients in underserved communities. Medical schools have the potential to close the gap when training future physicians by providing them with the principles of social medicine that can contribute to the reduction of health disparities. Curriculum reform and systematic formative assessment and evaluative measures can be developed to match social medicine and health disparities curricula for individual medical schools, thus assuring that future physicians are being properly prepared for residency and the workforce to decrease health inequities in the United States. We propose that curriculum reform includes an ongoing social medicine component for medical students. Continued exposure, practice, and education related to social medicine across medical school will enhance the awareness and knowledge for our students. This will result in better preparation for the zero mile stone residency set forth by the Accreditation Council of Graduate Medical Education and will eventually lead to the outcome of higher quality physicians in the United States to treat diverse populations.